Accelerate Ethnic Studies With “All Deliberate Speed!” - Sullivan, Talisa; Flores, Peter (Journal for Leadership, Equity, and Research, 2023)
America is known as the Land of Opportunity, yet one may ask, “Opportunity for whom?” Black/African American, Hispanic/Chicano/a/x/ Latino/a/x, Native American/American Indian, Asian American, and Pacific Islander along with other traditionally and historically underrepresented groups have experienced being marginalized in the United States as well as the school systems within our society. Since the inception of the concept of schooling in the United States, public education has had a minimal acknowledgment of historically and traditionally marginalized groups as contributors to the cultivation and development of the United States. It’s beyond time to redesign our educational system to reflect a system that will contribute to a true and sustainable democracy. This will require social justice educators with the capacity to teach our youth the complete truth of their cultural and ethnic imprint within the history and fabric of our country.